On certain analytic univalent functions. (1st February 2001) - Frasin, B. A.; Darus, M.
Abstract : We consider the class of analytic functionsB ( α ) to investigate some properties for this class. The angular estimates of functions in the classB ( α ) are obtained. Finally, we derive some interesting conditions for the class of strongly starlike and strongly convex of orderα in the open unit disk.